Histopathologic comparison of dexmedetomidine's and thiopental's cerebral protective effects on focal cerebral ischemia in rats - Ebru Çanakçı; Sevilay Akalp Özmen; Mustafa Ferhat Çolak; Hüsnü Kürşad (Brazilian Journal of Anesthesiology, 2016)
This study was designed to investigate whether dexmedetomidine and thiopental have cerebral protective effects after focal cerebral ischemia in rats. Thirty male Sprague Dawley rats were randomly assigned to three groups: control group (Group C, n = 10), dexmedetomidine group (Group D, n = 10), thiopental group (Group T, n = 10). After all rats were anesthetized, they were intubated, then mechanically ventilated. A catheter was inserted into the right femoral artery for continuous mean arterial pressure, physiological parameters and blood sampling at baseline, 5 min after occlusion and 20 min after reperfusion. A catheter was inserted into the left femoral vein for intravenous (IV) medication administration. Right common carotid artery of each rat was isolated and clamped for 45 min. At the end of the duration common carotid artery were unclamped and the brain reperfusion was achieved for 90 min. Dexmedetomidine was administered for Group D IV infusion, and Group T received thiopental IV. According to histopathologic scores cerebral ischemia was documented in all rats in Group C, but no ischemia was found in three rats in Group T and in four rats in Group D. Grade 3 cerebral ischemia was documented in three rats in Group C, and in only one rat in both groups T and D. For histopathologic grades the difference between Group T and Group D was not significant (p > 0.05). But the differences between Group C and Group T (p < 0.05) and Group C and Group D (p < 0.01) were statically significant. In conclusion, we demonstrated that dexmedetomidine and thiopental have experimental histopathologic cerebral protective effects on experimental focal cerebral ischemia in rats. Resumo: Este estudo foi desenhado para investigar se dexmedetomidina e tiopental possuem efeitos protetores cerebrais após isquemia cerebral focal em ratos. Trinta ratos da linhagem Sprague Dawley foram randomicamente alocados em três grupos: controle (Grupo C, n = 10), dexmedetomidina (Grupo D, n = 10) e tiopental (Grupo T, n = 10). Após a anestesia, todos os ratos foram intubados e ventilados mecanicamente. Um cateter foi inserido na artéria femoral direita para monitoração contínua da pressão arterial média (PAM), dos parâmetros fisiológicos e para coleta de amostras de sangue na fase basal, 5 minutos após a oclusão e 20 minutos após a reperfusão. Um cateter foi inserido na veia femoral esquerda para administração intravenosa (IV) de medicamentos. A artéria carótida comum direita de cada rato foi isolada e pinçada durante 45 minutos. Ao final dos 45 minutos, o pinçamento foi removido e a reperfusão do cérebro foi obtida por 90 minutos. Dexmedetomidina foi administrada por infusão IV no Grupo D e thiopental no Grupo T. De acordo com as pontuações histopatológicas, isquemia cerebral foi observada em todos os ratos do Grupo C, mas não foi encontrada em três ratos do Grupo T e em quatro ratos do Grupo D. O grau 3 de isquemia cerebral foi observado em três ratos do grupo C e em apenas um rato de ambos os grupos T e D. Para os graus histopatológicos, a diferença entre o Grupo T e o Grupo D não foi significativa (p > 0,05). Porém, as diferenças entre o Grupo C e o Grupo T (p < 0,05) e entre o Grupo C e o Grupo D (p < 0,01) foram estatisticamente significativas. Em conclusão, demonstramos que dexmedetomidina e tiopental possuem efeitos histopatológicos protetores cerebrais sobre isquemia cerebral focal experimental em ratos. Keywords: Brain ischemia, Dexmedetomidine, Thiopental, Neuroprotection, Palavras-chave: Isquemia encefálica, Dexmedetomidina, Tiopental, Neuroproteção